2012
DOI: 10.2174/1874306401206010097
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression Symptoms in Patients with Sleep-Disordered Breathing

Abstract: Introduction:Information concerning the frequency of anxiety and depression symptoms in patients with sleep-disordered breathing (SDB) is controversial. Hence, the objectives of this study were to: determine the frequency of anxiety and depression symptoms in patients with SDB; explore whether the frequency of anxiety and depression symptoms rises with increasing parameters of SDB severity; and investigate the factors potentially associated with anxiety and depression.Materials and Methodology:Data was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20] Several explanations for the differences in these observations are possible. Firstly, it could be suggested that sleep apnea affects mood differently in people who are aware of their sleep apnea and that this difference might explain the conflicting results between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17][18][19][20] Several explanations for the differences in these observations are possible. Firstly, it could be suggested that sleep apnea affects mood differently in people who are aware of their sleep apnea and that this difference might explain the conflicting results between studies.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 One study in patients with sleep apnea suggest that there is an association of low oxygen saturation with depressive symptoms but not between the apnea hypopnea index (AHI) with depressive symptoms, 14 whereas other studies suggest no association between indicators of sleep apnea severity with depressive symptoms. [15][16][17] A study including persons with suspected sleep apnea reported no consistent association between the severity of respiratory disturbances and depressive symptoms. 18 This is in line with results obtained from a large study of the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, reduced quality of life, anxiety, and depression have also been described. 11,15 Sleep disturbances, such as SDB, may from a pathophysiological perspective affect the development of early atherosclerosis (i.e. by an increased sympathetic activation), and as a consequence increase the risk of vascular dementia in patients with CHF.…”
Section: Introductionmentioning
confidence: 99%
“…Life time prevalence of generalized anxiety disorder in general population is 5.7% [4] . In contrast, 18.5% of patients with sleep disordered breathing had anxiety in one study [5] . In a study conducted by Sharafk haneh et al, [3] the prevalence of anxiety among patients with OSA was reported to be 16.67% and depression was 21.75% [3] .…”
Section: Introductionmentioning
confidence: 80%